The Efect of Breastfeeding Father to Breastmilk Production of Postpartum Mother - Yeni Kartika Sari; Anita Rahmawati (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2014)
Many postpartum mothers in Indonesia can not be exclusively breastfed their babies because the breast milk could not be produced smoothly. This is due to postpartum mothers often having experience emotional disturbances which inhibit the release of oxytocin and milk. Breasfeeding father is an active role and involvement of the husband to give moral and emotional support in breastfeeding to release chemical reflexes to produce milk. This research aims to find out the effect of the application of breastfeeding-father to breast milk production. This research was one group time series design. The population of this research was all of normal deliveries of postpartum mothers in puerperal room in Mardi Waluyo Blitar Hospital. The samples selected based on writers for 30 amount people that will be measured their milk production,  breastfeeding  and  the  application  of  breastfeeding  Father,  then  was  given counseling about breastfeeding father and asked to implement it. The data was analized using chi-square test to figure out the difference of breastmilk production between groups applying breastfeeding father and the group did not. The results showed there was differences of breast milk production between groups that applying breastfeeding father and the group did not. So the breastfeeding father could apply the breastfeeding postpartum mothers to increase the breast milk production.